Ḍolā-Mārūrā dūhā : Rājasthānī kā eka suprasiddha pracīna loka-gīta ; pāṭhāntara, Hindī anuvāda, ṭippaṇī, Śabda-kosha, pariśishṭa aura prastāvanā ke sātha sampādita - Siṃha, Rāma, 1902-1976; Pārīka, Sūryanārāyaṇa, 1902-1939; Dāsa, Narottama, Swami, 1905- (SAMP early 20th-century Indian books project, 1934)
Old Rajasthani love balled.